The Relationship Between Principals’ Leaderships Towards TVET Teachers’ Motivation in Implementing ICT - M Mohd Siraj, Mohd Asraf; Md. Rami, Ahmad Aizuddin; Omar, Rosmaria; Abdul Aziz, Nor Azni; Mohd Anuar, Mohd Ashraff (Journal of Technical Education and Training, 2023)
The leadership role in a school organisation is crucial for long-term success, particularly in relation to teachers’ motivation, especially in the implementation of ICT. School leaders possess the opportunity to employ diverse leadership styles that can influence teachers’ motivation, specifically in integrating ICT into teaching and learning. Technical and vocational education is an area where ICT integration holds significant potential for productivity enhancement, given its pivotal role in developing students’ college-ready skills. However, previous studies have shown uncertainties in the relationship between principals’ leadership styles and teachers’ motivation in certain schools. Therefore, this study aims to examine the relationship between principals’ leadership styles and TVET teachers’ motivation in implementing ICT. A correlational study was conducted, employing survey methods, and utilizing the Principal Instructional Management Rating Scale (PIMRS) for instructional leadership styles and the Multifactor Leadership Questionnaire (MLQ) for transformational leadership styles. The instruments used to measure teachers’ motivation were adapted from the instruments aligning with the TAM model. Data analysis included percentage, mean, standard deviation, frequency, regression, and Pearson’s correlation analysis, with a significance level set at p = 0.05. The results revealed that TVET teachers’ responses to the leadership styles of school principals in Malaysia are satisfactory. Furthermore, a significant correlation exists between the principal’s leadership styles and TVET teachers’ motivation. In addition, regression analysis demonstrates that transformational dan instructional leaderships influence TVET teachers’ motivation in implementing ICT. These findings provide support for previous research indicating that the principal’s leadership styles indeed influence teachers’ motivation.